Renewable Energy Consumption and Growth in Eurasia - Apergis, Nicholas; Payne, J. (Elsevier, 2010)
This study examines the causal relationship between renewable energy consumption and economic growth for 13 countries within Eurasia over the period 1992–2007 within a multivariate panel data framework. The heterogeneous panel cointegration test reveals a long-run equilibrium relationship exists between real GDP, renewable energy consumption, real gross fixed capital formation, and labor force. The results from the error correction models indicate bidirectional causality between renewable energy consumption and economic growth in both the short-run and long-run. Thus, the empirical findings lend support for the feedback hypothesis of the interdependent relationship between renewable energy consumption and economic growth.